A case of right aortic arch with isolated left innominate artery and global cerebral white matter atrophy. (10th August 2019) - Binka, Edem; Sun, Lisa R.; Gailloud, Philippe; Chiu, Joanne S.
Abstract: A right aortic arch with an isolated left innominate artery is a rare form of aortic arch anomaly. We present a case of neonatal diagnosis of this anomaly with concerning findings of global cerebral white matter atrophy at 13 months of age.